Performance competencies of the giri tirta sari drinking water Perumda Wonogiri District - Bambang Anggono; Istiatin Istiatin; Sudarwati Sudarwati (Jurnal Mantik, 2024)
In this research the author used a quantitative approach method with a pattern of giving questionnaires to respondents. This research was carried out by Perumda Air Minum Giri Tirta Sari, Wonogiri Regency, with the consideration that this agency requires internal control, work professionalism, work awards and competencies related to employee performance. Selection of research locations through observation to find out the general description of the agency. The research period was carried out for 2 (two) months from February 2022 to March 2022. The population in this study was all internal controls in the Giri Tirta Sari Drinking Water Company, Wonogiri Regency, totaling 238 employees. In this study the sample was calculated as 25% of the total population, namely 60 people. The sampling technique used was proportionate stratified random sampling. The analytical tool in this research is Multiple Linear Regression with the help of SPSS 24.Based on the results of the research that has been conducted, it can be concluded that internal control has a positive and significant effect on performance. Professionalism has a positive and significant effect on performance. Awards/rewards do not have a significant effect on performance. Competence has a positive and significant effect on employee performance. Internal control, professionalism, appreciation/reward, and competence simultaneously influence performance. The variables selected/entered into the model are correct, namely the variance of internal control variables, professionalism, appreciation/rewards, and competence in contributing/contributing to performance is 56.1%, the remaining 43.9% is influenced by other variables outside the model